1987
DOI: 10.1139/y87-013
|View full text |Cite
|
Sign up to set email alerts
|

Mise en évidence in vitro de la biosynthèse d'histamine à partir de carnosine par le rein de souris gravide

Abstract: Kidneys of pregnant mice synthesize histamine when incubated in the presence of carnosine, manganese, and pyridoxal phosphate. Intensity of biosynthesis increases linearly with the amount of enzyme and the incubation time. The reaction can only be catalysed by two enzymes that are located in kidneys and act in succession: carnosinase, which hydrolyzes carnosine into its two moieties, and histidine decarboxylase, which transforms histidine, a product of carnosine degradation, into histamine. The biosynthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…However, our immunohistochemical assay did not detect carnosine or related compounds in rat kidney. Arnould [17] showed that an extract of pregnant mouse kidney converted added carnosine into histamine, however the kidney was not assayed for endogenous carnosine.…”
Section: A)mentioning
confidence: 99%
“…However, our immunohistochemical assay did not detect carnosine or related compounds in rat kidney. Arnould [17] showed that an extract of pregnant mouse kidney converted added carnosine into histamine, however the kidney was not assayed for endogenous carnosine.…”
Section: A)mentioning
confidence: 99%
“…Arnould [17] identified carnosine in the kidneys of pregnant mice and documented increased activity of the histamine-synthesizing enzyme histidine decarboxylase as pregnancy progressed, and Cianciaruso et al [18] de monstrated that the dog kidney takes up carnosine and releases histidine regardless of the type of diet (histidinefree versus histidine-replete) being provided. Others, such as Abboud et al [19], have noted an increase in histamine synthesis in kidneys of rats treated with puromycin to cause nephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work from this laboratory [9 15] and others [16][17][18] has clearly de monstrated a link between carnosine, free histidine and histamine synthesis following surgical trauma, infection, femur fracture, wounding, pharmacologic stress and pregnancy. These studies support our hypothesis that carnosine serves as a non-mast cell histidine reservoir available for histamine synthesis following trauma or stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations